Pendidikan Islam Dalam Perspektif Imam Al-Ghazali dan KH. Moh. Idris Jauhari - Ahmadi Ahmadi; Allivna Miyazaky Naufal (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2020)
This article will discuss Islamic Education in the perspective of Imam Al-Ghazali and KH. Moh. Idris Jauhari. It was these two figures who, in subsequent developments, were able to reconstruct the concept of Islamic education in accordance with the realities and needs of the times. This study is expected to be able to explain the meaning of educational methods, educational meanings, educational goals, educational materials, educational curricula, educational concepts, educational systems, educational instruments, the Qur'an and Hadith as the basis of education, useful knowledge, and educational methods. This research uses the method of library research. The data sources used are works related to Al-Ghazali and KH. Moh. Idris Jauhari. From the research results, it was found that the similarities and differences in the thoughts of the two figures regarding the understanding of educational methods, the meaning of education, educational goals, educational materials, educational curricula, educational concepts, educational systems, educational instruments, Al-Qur'an and Hadith as educational foundations, useful knowledge , and educational methods.